THE EFFECTIVENESS OF THE IMPLEMENTATION OF GOVERNMENT SOCIAL POLICY: METHODOLOGICAL APPROACHES TO EVALUATE AND INTERNATIONAL PRACTICE TO ENSURE IT - Pomaza-Ponomarenko A.L. (Pressing Problems of Public Administration, 2016)
The analysis of the condition of  nancial support of the state social policy in the economicallydeveloped countries and in Ukraine was made. The idea about the in uence of the GDP growth ratesdynamics on the share of social expenditures of these states was expressed and veri ed.